Assessment of the Present State and Economical Prospects of Solid Waste at Amin Bazar Waste Dumping Site, Dhaka, Bangladesh (Journal of Scientific Research, 2015)
The study was conducted to explore the current status and the economical prospect of the solid waste management at Amin Bazar waste dumping site, Dhaka. A total of 48 waste samples were collected in both dry and wet season to study the physical composition, pH and moisture content of discarded wastes. The wastes were comprised of plastics (6%), paper (3.5%), glass (0.23%), garden waste (8.5%), food stuffs (72.25%), metals (0.16%) and textile products (3.25%). The pH values of the samples were ranges between 6.9-7.8 indicated the neutral condition. Larger portion of the wastes was organic (72%). About 14.38% of waste was recyclable but there is no recycling and composting facility. Proper recycling of the solid wastes at Amin Bazar can be a source of compost and useful metal resources which may contribute in safe and sustainable environmental management.